Online forum discussion: From the perspectives of college students - Wong, Ling Shing (2010)
Online forum gains its weight in our daily life and it can serve as a tool for constructive learning. Survey on 39 students after been given an online forum discussion as assignment discovered that 95% of them never being exposed to this type of formal assignment before that. However, about 67% of them knew that they can acquire scientific knowledge through online forum discussion. Around 54% of the respondents agreed that online forum discussion had motivated them in their learning process, while 72% of them found that the discussion had inspired their creativity. About 59% of them found that the discussion had elevated the interaction between their course mates. The respondents named the most attractive point of online forum discussion was less interference from the instructor, while the least attractive, the relatedness to the syllabus. From 32 respondents, who were frequent internet users, 78% of them could accept the usage of online forum discussion as formal assignment in future, while among the non-frequent was 50%. About 41% of the frequent internet users could accept the usage of online forum discussion in replacement of formal face-to-face lecture, while there were only 14% for non-frequent users. As been found motivating, inspiring the creativity, and increase the interaction by majority students, online forum discussion is a good tool for constructive learning, especially for the frequent internet users.